Pharmacy Technicians, Pharmacists, Nurses, and Microbiologists in Tackling Antimicrobial Resistance: Current Strategies and Future Directions - Ibtisam Hussain Hudani; Areeg Yahya Rasheed Moathanah; Salha Yahia Khalil; Mashael Ahmed Wali Hakami; Ibrahim Ahmad Masmali; Atyaf Essa Ahmed Dahlan; Dalia Abkar Daws; Fatimah Eid Alenezi; Zaniab Abdu Hanin; Eman Hasan Hakami (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Antimicrobial resistance (AMR) is a significant issue, leading to increased morbidity, mortality, and expenses, with sub-Saharan Africa exhibiting the highest rates worldwide. Concerns over the escalation of AMR have prompted worldwide, Pan-African, and national initiatives, including the formulation of national action plans (NAPs). Aim of work: To explore the alarming rise of AMR in critical care settings and investigate the role of pharmacy technicians, pharmacists, nurses, and microbiologists in tackling AMR Methods: The keywords ” Pharmacy Technicians, Pharmacists, Nurses, and Microbiologists, Tackling Antimicrobial Resistance” were used to conduct a thorough literature search in the MEDLINE database in order to find relevant publications published between 2017 and 2024. Using the proper search terms, Google Scholar was utilized to find and access pertinent scientific publications. Various inclusion criteria were used to choose which articles to select. Results: The research included in this study was published from 2017 to 2024. The research included a discussion segment that was broken into many specific elements. Topics covered include the Pharmacy contributions in combating AMR, Nursing role in tackling AMR, Microbiology Laboratory role in AMR. Conclusion: Integrating pharmacists into healthcare systems can reduce antibiotic misuse in underdeveloped nations. This can be achieved through improved positions, university curricula, and professional development. Hospitals should implement antimicrobial stewardship to ensure responsible use. Nurses play a crucial role in AMS and patient safety, but their knowledge and reluctance to speak up limit their contribution. Pre- and post-registration education, voicing concerns, and strong hospital leadership can maximize their contribution. The Microbiology Laboratory is essential for infection control, and new techniques can transform prevention and control tactics.